An investigation into the implementation of the disciplinary procedure manual of the Department of Correctional Services : the case of Polokwane Management Area - Mabotja, K. R. (University of Limpopo, 2007)
Refer to the document
Thesis (MPA.) -- University of Limpopo, 2007
Keywords: Disciplinary procedure manual; Labor discipline -- Handbooks, vade-mecums, etc.; Labor discipline -- South Africa